Flame‐retardant behavior and protective layer effect of phosphazene‐triazine bi‐group flame retardant on polycarbonate. Issue 46 (12th June 2020) - Chen, Yajun; Wu, Xingde; Qian, Lijun
Abstract: A series of flame‐retardant polycarbonate (PC) composites with different ratios of phosphazene‐triazine bi‐group flame retardant (A3) were prepared. The flame retardant performance and thermal stability of PC/A3 composites were characterized by LOI, UL 94 vertical burning test, cone calorimetry test and TG. Results show that when the addition of A3 is 13.5%, the PC/A3 composite can pass UL94 V‐0 level with a LOI value of 29.3% and reduce the peak heat release rate by 47.5% during the combustion. TG results show that adding 5% A3 can increase the initial decomposition temperature of the PC by 7°C in nitrogen and 9°C in air. Investigation of the morphology and chemical structure of char residue demonstrates that A3 promotes the formation of more complete and compact char residue which acts as physical barriers to inhibit the transfer of heat and oxygen, resulting the good flame retardant properties. The analysis of gaseous pyrolysis product reveals that A3 also exerts a flame‐retardant effect in gas phase by releasing PO· free radicals. Abstract :